Contribution of Work Discipline, Motivation, Work, and Work Environment to Teacher Performance - Khairuddin Khairuddin; Saut Purba; Aman Simaremare (Randwick International of Education and Linguistics Science Journal, 2024)
The aim of this research is to analyze the contribution of: (1) work discipline to teacher performance; (2) work motivation to teacher performance; (3) work environment to performance; and (4) discipline, work motivation, and work environment simultaneously to teacher performance. The research was carried out at state elementary schools in Rantau Utara District, Labuhanbatu Regency. The research population was 396 teachers, and the research sample was 162 teachers. The sampling technique employed in the study involved the use of Isaac and Michael tables along with probability sampling methods. The results of research on simultaneous performance are 80.51%, 3.74%, and 15.76%, meaning that work discipline is the most dominant factor in influencing teacher performance. Teachers who are disciplined in carrying out their duties, show high commitment, are able to manage their time well, and comply with established rules and procedures. Even though the percentage is small, work motivation is an important factor in improving teacher performance. Teachers who have high work motivation will be encouraged to work more enthusiastically, creatively, and innovatively in teaching. A conducive and supportive work environment can help improve teacher performance by providing adequate facilities and infrastructure, creating a positive work atmosphere, and providing opportunities for teachers to develop themselves professionally. Teachers who demonstrate a high level of work discipline tend to contribute to increased performance in carrying out tasks; teachers who have work motivation tend to contribute positively to increased teacher performance; and a conducive work environment tends to contribute to increased overall teacher performance.